Exploration of anti-tumor activity of erlotinib derivatives enabled by a Pd-catalyzed late-stage Sonogashira reaction. (13th February 2023) - Sun, Lian; Feng, Rui; Zhen, Yong-Qi; Hou, Zong-Rui; Li, Xiaohuan; Shan, Lian-Hai; Gao, Feng
Abstract: Fifty-eight erlotinib derivatives were designed and synthesized efficiently by the late-stage functionalization (LSF) strategy, directly installing the aryl, hetero aryl, and vinyl groups into the alkynyl group of the anticancer drug erlotinib. A new Palladium-NiXantphos catalyzed system of Sonogashira reaction was developed to accomplish the LSF of erlotinib. Both sp-sp 2 coupling and sp-sp 3 coupling could be achieved by the catalyst system. The reaction features mild, clean, high chemo-selectivity, and good functional group tolerance. Five compounds (3d, 3l, 5i, 5p, and 7c ) showed potent cytotoxicity against A549 cancer cell lines. Compound 3l displayed excellent activity with IC50 11.4 μM, better than that of erlotinib (IC50 35.5 μM). Graphical abstract: Image 1